Examining the job burnout of Chinese hospitality management students in internships via the transactional model - Yin, Xiao L.; Yang, Yan L.; Kim, Hyung J.; Zhang, Yan (Frontiers in Psychology, 2022)
The ongoing COVID-19 pandemic has increased the psychological burden on employees in hotels, which is not conducive to the development of the hospitality industry. Based on a survey of 379 hotel interns from higher vocational colleges in China, this study empirically analyzed the status quo of job burnout in future hotel employees and its influencing factors. The results showed that interns’ job burnout and reduced personal accomplishment were at a medium level. Secondly, according to the transaction model, this study classified the antecedents of job burnout into two categories: personal factors and contextual factors. The results showed that personal factors such as attitude and self-efficacy, and contextual factors such as perceived co-worker support and job satisfaction all had a negative effect on job burnout. However, the influence of ability and perceived supervisor support on job burnout was not significant. This study also investigated the influencing factors of each sub-dimension of job burnout. Self-efficacy, attitude and job satisfaction all had a negative influence on the three sub-dimensions. Ability and perceived co-worker support only had a negative impact on reduced personal accomplishment. There was no statistical correlation between perceived supervisor support and the three sub-dimensions. The results of this study will lay a theoretical foundation so that higher vocational colleges can better organize and implement internships, and hotels can recruit energetic future employees.